Analisis Seni Gambar Kaligrafi Santri Madrasah Aliyah Kelas XI Usia 16-17 Tahun di Pesantren Al Aulia Bogor Barat - Putri, Safira; Oetopo, Ataswarin (Program Studi Pendidikan Seni Rupa FBS UNJ, 2023)
The purpose of this research is to analyze the art of calligraphy painting, as well as to find the meaning of each Qur'anic verse in the work and its implementation. It is based on the background of the fact that the factor in drawing calligraphy is more supportive of Qur'an reading and writing activities or can support the Qur'an tahfiz program and can be a material in preaching, improving the characteristics of santri / nun children to be better guided by the book of the Qur'an. The theories used for this research include Nasir's theory on the definition of religious institutions, Hakim's theory on the pesantren education model, Victor Lownfeld's